Teaching as a design science building pedagogical patterns for learning and technology - Laurillard, Diana, 1948- (New York, NY Routledge, 2012)
"Teaching is changing. It is no longer simply about passing on knowledge to the next generation. Teachers in the 21st century, in all educational sectors, have to cope with an ever-changing cultural and technological environment. Teaching is now a design science. Like other design professionals - architects, engineers, town planners, programmers - teachers have to work out creative and evidence-based ways of improving what they do. But teaching is not treated as a design profession. Every day, teachers design and test new ways of teaching, using learning technology to help their learners. But their discoveries remain local. By representing and communicating their best ideas as structured pedagogical patterns, teachers could develop this vital professional knowledge collectively. Teacher professional development has not embedded in the teacher's everyday role the idea that they could discover something worth communicating to other teachers, or build on each others' ideas. Could the culture change? From this unique perspective on the nature of teaching, Diana Laurillard argues that a 21st century education system needs teachers who work collaboratively to design effective and innovative teaching"-- Provided by publisher.
Teaching as a design science -- What is formal learning? -- What students bring to learning -- What it takes to learn -- What it takes to teach -- Motivating and enabling the learning cycle -- Learning through acquisition -- Learning through inquiry -- Learning through discussion -- Learning through practice -- Learning through collaboration -- Teaching as developing pedagogical patterns
Includes bibliographical references and index.
Keywords: Teaching -- Philosophy; Professional learning communities; Educational technology; Electronic books